On universal coding events in protein biogenesis. (February 2018) - Kubyshkin, Vladimir; Acevedo-Rocha, Carlos G.; Budisa, Nediljko
Abstract: The complete ribosomal protein synthesis cycle and codon-amino acids associations are universally preserved in all life taxa on Earth. This process is accompanied by a set of hierarchically organized recognition and controlling events at different complexity levels. It starts with amino acid activation by aminoacyl tRNA synthetases (aaRS) followed by matching with the acceptor units of their cognate tRNAs ("operational RNA code") and ribosomal codon-anticodon pairing of messenger RNA ("triplet code"). However, this codon-anticodon matching is possible only when protein translation machinery (translation factors, ribosome) accepts an esterified amino acid. This capacity ("charge code") correlates mainly with the amino acid nature and the identity elements in the tRNA 3D structure. A fourth potential "folding code" (also referred as "stereochemical code") between the translation dynamics, sequence composition and folding of the resulting protein can also be defined in the frame of the 'Anfinsen dogma' followed by post-translational modifications. All these coding events as well as the basic chemistry of life are deemed invariant across biological taxa due to the horizontal gene transfer (HGT) making the 'universal genetic code' the 'lingua franca' of life of earth. When cells (or organelles) are prevented from transmitting genetic information (i.e., HGT) the deviations in the above-mentioned coding events become inevitable. A better understanding of these codes, in particular the mechanisms of their conservation in the context of HGT could provide a guide for the experimental engineering 1 of the ribosomal protein biosynthesis machinery. This is highly relevant, among others, in attempts to create synthetic life forms in genetic isolation by using tailored "minimal genomes" and may explain the necessity for multiple coding evens in nature.